Vertical aerated recycled concrete aggregate filter for removal of phosphorus - Adnan, Suraya Hani; Abd Roni, Norwardatun (UTHM Publisher, 2018)
This paper assesses a new design of recycled concrete aggregates as vertical aerated filter for removal of phosphorus (P). Recycled concrete aggregates (RCA) obtained from crushed concrete waste. In this study, RCA is used as an Aerated Filter for removal of P. A commercial concrete was crushed, and the RCA were sieving according to different sieve size. The highest percentage passing sieve size is size 5 mm to 10 mm is 99.54%. The pH value for RCA is 9.30 which is alkaline. RCA with smallest size and lowest initial concentration of P which is 5mm to 10 mm and 10 mg/L respectively has the lowest uptake capacity which 0.995 mgL-1/g. Moreover, the RCA also contain Phosphorus (P) element which is that it proven for us that RCA has a high capacity for absorbing phosphorus. After a few months in the aerated filter system, phosphorus can be seen on the surface of RCA samples after being examined by EDX test. The usage of RCA will ease the environmental problems that are currently perceived globally. RCA could also saves landfill space which helps reduce the needs for gravel mining and reduces pollution